Influence of Applied Voltages on Mechanical Properties and In-Vitro Performances of Electroplated Hydroxyapatite Coatings on Pure Titanium. Issue 7 (1st January 2016) - Chen, Shih-Hsun; Tsai, Wei-Lin; Chen, Po-Chun; Fang, Alex; Say, Wen-Ching
Abstract : Titanium and its alloys have been extensively used in biomaterials due to their bone-compatible modulus, superior bio-compatibility and enhanced corrosion resistance. But the metal implants that contact the body will release ions and scraps. In this study, Hydroxyapatite (HA, Ca10 (PO4 )6 (OH)2 ) was coated on a pure Ti substrate by electrochemical deposition process, which can provide a well-controlled process and product. Across various applied voltages, the electroplated HA/Ti composites were evaluated on their chemical and mechanical performances and the behaviors of in-vitro simulating tests. Highly pure HA coatings were obtained with additional voltages from 16 V to 19 V. In addition, their mechanical properties were significantly enhanced with increasing voltages. With the results of in-vitro evaluations, the electroplated HA/Ti composites is capable of serving as a biomaterial for bone substitution or implantation.